Monkeypox in Liver Transplant Patient - Genzini , Tércio; Santos, Regina Gomes dos; Rodriguez , Tomas Navarro; Stucchi, Raquel Silveira Bello; Fonseca, Luís Edmundo Pinto da; Marzinotto , Maira Andrade Nacimbem; Figueiredo, Sabrina Rodrigues de; Rodrigues, Marina Guitton; Almeida, Thais Natália de; Perosa , Marcelo (Brazilian Journal of Transplantation, 2023)
Monkeypox (MKP) is a zoonosis caused by a DNA virus belonging to the Orthopoxvirus genus in the Poxviridae family and was isolated for the first time in Denmark, in 1958. In 1970, the first case in humans was described in the Democratic Republic of Congo and, since then, it has spread with inter-human dissemination and, in July 2022, the WHO declared a state of health emergency. Its clinical presentation is similar to that of smallpox, with skin eruptions that evolve as macules, papules, vesicles, pustules and crusts. The first case in a transplanted patient was described in Thailand, in June 2022, in a bone marrow transplanted patient. In this report, we describe the case of MKP in a patient in the postoperative period of liver transplantation. We also discuss clinical aspects of this situation, which is still little known among the transplanter community.